Encyclopedia of chart patterns - Bulkowski, Thomas N., 1957- (Wiley trading., 2005)
In this revised and expanded second edition of the bestselling Encyclopedia of Chart Patterns, Thomas Bulkowski updates the classic with new performance statistics for both bull and bear markets and 23 new patterns, including a second section devoted to ten event patterns.